Pengaruh Film Animasi Ali dan Annisa terhadap Perkembangan Kemandirian Anak Usia 5-6 Tahun di TK Harapan Bangsa Kecamatan Patamuan - Indah, Wisma; Hartati, Sri (ANWARUL, 2023)
The purpose of this study was to determine the effect of the animated film Ali and Annisa on the development of children's independence in Harapan Bangsa Kindergarten, Patamuan District. This type of research is quantitative using experimental methods in the form of Quasi-Experimental (quasi-experimental). The population in this study were all children at Harapan Bangsa Kindergarten, while the samples were group B1 as the experimental class, and group B2 as the control class, with 12 children each. The data collection technique used by researchers is the behavioral test. Data analysis techniques using normality test, homogeneity test, and hypothesis testing. Hypothesis test obtained sig value at sig. (2-tailed) is 0.000. The value of 0.000 <0.05 means that there is a significant difference between the results of the pre-test and post-test using animated films and learning videos at Harapan Bangsa Kindergarten, Patamuan District, so that ani,ated films have an effect on independence in kindeergarten.